Estimation of turbulent velocity spectra from laser Doppler data - Benedict, L H; Nobach, H; Tropea, C (Measurement science & technology, 2000)
Reviews the problem of power spectral estimation from velocity data sampled irregularly in time by a laser Doppler anemometer (LDA) from very early estimators based on slot correlation to more refined estimators which build upon a signal reconstruction and an equidistant re-sampling in time. The discussion is restricted to single realization anemometry, ie, excluding multiple particle signals. Classifies the techniques and makes an initial assessment before describing currently used methods in more detail. A related subject, the simulation of LDA data, is briefly reviewed, since this provides a means of evaluating various estimators. Using the expectation and variance as figures of merit, the advantages and disadvantages of several estimators for varying types of turbulent velocity spectral distributions are discussed. A set of recommendations is put forward as a conclusion. (Original abstract)